Ecological factors affecting Infant at Work policies and programs in university settings. Issue 1 (3rd July 2021) - DeMaria, Andrea L.; Wierenga, Madison; Kelly, Kilian; Smith, Sidney; Bohning, Anna; Bauman, Tessa; Schwab‐Reese, Laura
Abstract: Objectives: This study identifies the ecological (ie, policy, environment, intrapersonal, and interpersonal) factors affecting the implementation of an Infant at Work program in a university setting. Methods: Data were collected among faculty, staff, and graduate students at a large Midwestern university from February to July 2020 via focus group (FG) discussions with university employees (n = 22) and semistructured interviews with university administrators (n = 10). We used techniques from expanded grounded theory, allowing for a constant comparative approach to data contextualization and theme identification. Results: Three themes emerged from the FG data: (i) program and policy scope, (ii) employee and employer benefits, and (iii) workplace concerns. Onsite daycares, flexible schedules and participation, and expanded childcare options were some of the programs and policies employees desired. However, barriers to implementing these types of programs include cost, safety, and structure of the work environment. Conclusions: Findings offer practical recommendations and strategies to improve work/life balance among parents transitioning back to work in a university environment. Findings also provide insight into the feasibility of family‐friendly workplace policies and environments. Additionally, findings provide a framework for other organizations to implement similar Infant at Work programs to improve employee work/life balance.